Long-term ovarian reserve and fertility outcomes in female survivors of childhood acute lymphoblastic leukemia. Issue 9 (29th July 2021) - Elitzur, Sarah; Frank, Shani; Goshen-Lago, Tal; Barzilai-Birenboim, Shlomit; Gilad, Gil; Avrahami, Galia; Goldberg, Tracie; Litichever, Naomi; Masarwa, Ameena; Oron, Galia; Yaniv, Isaac; Izraeli, Shai; et al.
Abstract: Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy, yet data regarding long-term ovarian reserve of female survivors are limited. The aim of this study was to investigate whether there is a differential pattern of anti-Mullerian hormone (AMH) levels in female childhood ALL survivors compared with the normal age-matched population. In a cohort of 56 female childhood ALL survivors (median age 29 years; median follow-up 20.6 years), a negative correlation was found between age at leukemia diagnosis and age-adjusted anti-Mullerian hormone (AMH) levels ( r = −0.334, p = .031). Despite alkylating agent therapy, AMH levels did not differ significantly from age-related nomograms (age < 30, p = .17; age ≥ 30, p = .94). The mean number of children per fertile woman adjusted for maternal age was similar to the national average (2.76 versus 3.11, p = .19). Our results imply that reproductive outcomes are not significantly hampered in female pediatric ALL survivors. Long-term surveillance of ovarian reserve may enable personalized survivorship counseling.